Computed tomographic study of occipital thickness in Malay ethnicity : a descriptive study - Govindasamy, Murali (2017)
Introduction: Occipito-cervical fusion is a procedure that is performed for cranio-cervical instability as well as certain conditions of atlanto-axial instability. Literature has suggested that a screw of at least 8mm is needed for biomechanical stability. Morphological data for occipital thickness of Malay ethnicity is poorly documented in literature and this study presents the optimal screw placement positions for occiput screw in those of Malay ethnicity. Methodology: This was a retrospective cross-sectional study of 100 subjects without disease of the head and neck who underwent Computed Tomography (CT) scan of the brain at Hospital Sungai Buloh. There were 57 males and 43 females with a mean age of 36.7 analyzed in this study. Measurements were taken using a specialized viewer box where 55 points were measured. These 55 points followed a grid with 10mm distance based taking the External Occipital Protuberance (EOP) as the point of reference. Results: The thickest bone of the occiput is at the EOP measuring 16.15mm. There was an area of at least 8mm thickness up to 20mm on either side of the EOP, and at level 10mm inferior to the EOP. There is thickness of at least 8mm, up to 30mm inferior to the EOP at the midline. The males have significantly thicker bone especially along the midline compared to females. Conclusions: Screws of at least 8mm can be safely inserted at 20mm on either side of the EOP and at the level 10mm inferior to the EOP. Screws of at least 8mm in length can also be inserted and up to 30mm inferior to the EOP at the midline